ANALISIS DEKONSTRUKSI WACANA SASTRA; CINTA, IDEOLOGI DAN RELASI KUASA DALAM DONGENG TROYA - Mashur Abadi (OKARA: Jurnal Bahasa dan Sastra, 2013)
This article talk about one of the fiction genre movie is a colossal epic movie. “Troy” is one of the example of epic movie. It is tell about Trojan war which based on a poem The Iliad and Odyssey by Homer. It also tells more about the heroism of Achilles (Brad Pitt) and Hector (Eric Bana). Generally, the true heroes always being honest and sincere in serve the society. However, thisepic move also shown us, that love, ideology and power relation also clear enough appear on the model of communication. The substance of this observation is the representation of love, ideology, and power relation by showing the bineary oposition that reflected in the story. This observation uses the semiotic analysis method. Analysis method is used to express the meaning of of love, ideology, and power relation of Troy movie. It is uses constructive perspective on binnary oposition and also critical literary discourse analysis, with emptive text analysis to express of love, ideology, and power relation. As shown in the film there is an opposite character of the heroism as on of the example of the data, Achilles and Hector, i.e Paris. Paris is a faint hearted person. Appears on his lack, such as small, thin body, immature, selfish and timid.